2021
DOI: 10.20527/jipf.v5i2.2871
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Bahan Ajar Elektronik Berbasis Multimodel pada Materi Alat-Alat Optik untuk Melatihkan Kemampuan Analisis Peserta Didik

Abstract: Kemampuan analisis peserta didik yang rendah mendorong diadakannya penelitian untuk melakukan variasi dalam kegiatan belajar mengajar. Tujuan penelitian adalah mendeskripsikan validitas dan kepraktisan bahan ajar elektronik berbasis multimodel yang dikembangkan untuk melatihkan kemampuan analisis peserta didik. Penelitian menggunakan tiga model pembelajaran yaitu model pengajaran langsung, model pembelajaran kooperatif (tipe STAD) dan model pembelajaran berbasis proyek. Penelitian yang dikembangkan adalah pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…This shows that digital learning material is useful, easy to use, the presentation is interesting, clear, and has integrated AR and CTL models. The practicality results for this digital learning material are helped by the research results which states that the material of learning developed have benefits for students as users, provide ease of use, and make learning time effective (Irhandayaningsih, 2020;Nida et al, 2021). In addition, previous study found there was an increase in student activity from the previous 72% to 90% (Nur et al, 2020).…”
Section: Discussionmentioning
confidence: 79%
“…This shows that digital learning material is useful, easy to use, the presentation is interesting, clear, and has integrated AR and CTL models. The practicality results for this digital learning material are helped by the research results which states that the material of learning developed have benefits for students as users, provide ease of use, and make learning time effective (Irhandayaningsih, 2020;Nida et al, 2021). In addition, previous study found there was an increase in student activity from the previous 72% to 90% (Nur et al, 2020).…”
Section: Discussionmentioning
confidence: 79%
“…A multimodel is a learning process that employs more than two or several models (Imron, 2021;Maria, 2010;Nida et al, 2021). Therefore, multiple learning models are utilized to teach physics lessons.…”
Section: Introductionmentioning
confidence: 99%
“…Nurhafizah et al (2015) and Zainuddin et al (2020) research demonstrates the feasibility of a physics module based on the interrelation between the Quran and science, as indicated by a module categorized as quite effective. In addition, the research findings of Nida et al (2021) indicate that multimodel-based electronic instructional materials tested with a student-oriented response questionnaire are practical. Consequently, electronic instructional materials can train students' analytical skills using multiple models.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of teaching materials in the form of modules is thought to be capable of assisting students in obtaining efficient learning resources; additionally, the electronic modules developed can be printed independently by students, making it easier for students to access them quickly and flexibly. According to Lailis et al (2019) in (Nida et al, 2021), the development of physics learning materials responsive to technological advancements makes it easier for students to access them via laptops or smartphones. The developed physics module, in conjunction with the multimodel, emphasizes the diversity of learning models regarding impulse material and linear momentum in improving problem-solving abilities, where learning that was previously teacher-centered is now studentcentered, and each meeting emphasizes the 7 steps of problem-solving.…”
Section: Introductionmentioning
confidence: 99%
“…This was in line with the research of (Salam et al, 2022), where multimodel-based learning was able to train higher-order thinking skills with an N-gain of 0.54 in the moderate category. In the research of (Nida et al, 2021), multimodel learning was thought to improve students' analytical abilities and thus increase student learning outcomes.…”
Section: Introductionmentioning
confidence: 99%